Kegiatan Senam Otak Anak Usia Dini - Yolanda Dwi Putri; Rivda Yetti (PG-PAUD Trunojoyo, 2019)
Brain exercise has many benefits, especially to balance the child’s brain and left, though brain gym activities can foster the spirit of learning children. This study describe brain gym activities carried out in the primagama padang creative kindergarden playgroup. This study uses qualitative methods with a descriptive approach. Data collection techniques are observation, interview and documentation, while the data analysis technique is data triangulation technique. The results of research in the primagama padang creative kindergarden playgroup that brain gym activities have been carried out well, seen from semester planning, weekly and daily planning and evaluations carries out in every brain gymnastic activity. The implementation of brain gym activities provides many benefits to children.